Bioelectrical impedance for detection offluid status and its role in dry weight adjustment in peritoneal dialysis patients with cardiorenal syndrome - ZHOU Jian-dong; XIE Feng-yan; LI Hui; XU Zhong-xiu (Linchuang shenzangbing zazhi)
Objective To detect fluid load by multifrequency bioelectrical impedance measurement and evaluate its role in dry weight adjustment in peritoneal dialysis(PD)patients with cardiorenal syndrome.Methods Forty cases of PD patients diagnosed with cardiorenal syndrome in the nephropathy center of our hospital were selected as the PD group,and 80 cases of healthy patients in our hospital were selected as the control group.For the patients in the PD group before and after dry weight adjustment and the patients in the control group,sex,age,body weight,blood pressure were recorded,and bioelectrical impedance values,including total water content in the body,extracellular water content and intracellular water content at 20 and 100 kHz,were measured.The heart indexes before and after dry weight adjustment in the PD group were measured by cardiac doppler ultrasound.In the PD group,24 patients whose dry weights was higher than the upper limit of the 95% confidence interval in both sides of the control group were selected,and their dry weight was gradually reduced gradually.The body weight,blood pressure and bioelectrical impedance of these patients were measured once again 2 months later.Results(1)The measured values of bioelectrical impedance in the PD group were higher than those in the control group,and the difference was statistically significant(P<0.01).The measured bioelectrical impedance of 24 PD patients after dry weight adjustment was higher than that of the control group,and the difference was not statistically significant.(2)The measured values of bioelectrical impedance in 24 PD patients after dry weight adjustment were significantly lower than those before the adjustment(P<0.05).The bioelectrical impedance of extracellular water content decreased dramatically(2.85±0.67)%.Systolic blood pressure and diastolic blood pressure in 24 PD patients decreased after dry weight adjustment,compared with those before dry weight adjustment,with statistically significant difference of systolic blood pressure.The left ventricular end-diastolic volume and left ventricular end-systolic volume decreased significantly compared with those before the downregulation,with statistically significant difference.Conclusions Multifrequency bioelectrical impedance measurement can be used to detect fluid load in peritoneal dialysis patients with cardiorenal syndrome,so as to adjust dry weight with reference to the normal range.